ASANA APPLICATION ORGANIZATIONAL COMMUNICATION AUDIT AT CHALIDANA GROUP - Ramadhani, Ghina; Arif Darmawan; Merry Fridha Tri Palupi (Media Inovasi Pendidikan dan Publikasi, 2024)
The development of communication technology has created innovations in the form of applications that can be used in the property industry as a tool for organizational communication, information, project management and company documentation. These applications include the Asana application. One of the property companies that has implemented the Asana application is Chalidana Group. This research is entitled Audit of Organizational Communication of the Asana Application at the Chalidana Group. The purpose of this research is to audit the socialization process in using the Asana application, analyze communication barriers in using the Asana application, and evaluate the achievement of organizational communication through the Asana application at the Chalidana Group. This research uses a qualitative research method with a Communication Audit approach, and data collection techniques through interviews, observation and documentation. The results of the Communication Audit research showed that the socialization process for using the Asana application was delivered face-to-face by the Project Manager through meetings and workshops held at the Chalidana Group office. The obstacles that researchers found were limited understanding of the development of information and communication technology and language barriers caused by the limited knowledge possessed by the project team. It is hoped that this research can contribute to further understanding of the use of the Asana application in the context of organizational communication, as well as provide useful insights for companies in optimizing the use of this application. The results of this research show that Asana provides significant benefits for the Chalidana Group for by improving better project management collaboration, tracking and monitoring work tasks, as well as effective communication between the management teams involved.